НЕКОТОРЫЕ ПРОБЛЕМЫ СТАНОВЛЕНИЯ ПРАВОВОГО ГОСУДАРСТВА В РЕСПУБЛИКЕ КАЗАХСТАН В ПЕРИОД ТРАНЗИТНОГО ОБЩЕСТВА (Journal of actual problems of jurisprudence, 2019)
In this article the author writes about some problems of rule of law in the Republic of Kazakhstan in the period of transitcompany